Laparoscopic cholecystectomy conversion rate and associated factors - Osman , Mohd Firdauss (2011)
Objective: To identify risk factor/s for conversion to open cholecystectomy. Methodology A retrospective records review was carried out. Records of all patients who underwent laparoscopic cholecystectomy from January 2008 till December 2009 in Hospital Raja Perempuan Zainab II (HRPZ II), Kota Bharu, Kelantan were reviewed and all risk factors were documented. Risks factors for conversion were analysed. Results Of 82 records reviewed, 11 (13.4%) require conversion to open cholecystectomy. Age, gender, co-morbidity and history of prior abdominal surgery were not statistically significant to the conversion rate. Fever, pancreatitis and ultrasound findings of thickened gallbladder wall or pericholecystic fluid collection were not associated with significant risk of conversion. There were significant associations between acute cholecystitis (p-value=0.06, adjusted OR=13.365) and stone in the common bile duct (p-value=0.07, adjusted OR=9.278) with conversion to open cholecystectomy. Conclusion Acute cholecystitis and presence of stone in the common bile duct were associated with higher incidence of conversion to open cholecystectomy